+0  
 
0
42
3
avatar

SImplify  $$\dfrac{7x^{2014}}{4x^{2013}}\cdot{\dfrac{2x^{2012}}{2x^{2007}}}\cdot\dfrac{27x^{2006}}{x^{2002}}\cdot\dfrac{6x^{2008}}{8x^{2010}}.$$

 May 5, 2022
 #1
avatar+117116 
+2

I will start you off.

 

 

\(\dfrac{7x^{2014}}{4x^{2013}}\cdot{\dfrac{2x^{2012}}{2x^{2007}}}\cdot\dfrac{27x^{2006}}{x^{2002}}\cdot\dfrac{6x^{2008}}{8x^{2010}}\)

 

 

 

\(=\dfrac{7x^{2014-2013}}{4^{2013}}\cdot{\dfrac{2x^{2012}}{2x^{2007}}}\cdot\dfrac{27x^{2006}}{x^{2002}}\cdot\dfrac{6x^{2008}}{8x^{2010}}.\\ ~\\=\dfrac{7x^{1}}{2^{2*2013}}\cdot{\dfrac{2x^{2012}}{2x^{2007}}}\cdot\dfrac{27x^{2006}}{x^{2002}}\cdot\dfrac{6x^{2008}}{8x^{2010}}\)

 

 

Now it is your turn.

 May 6, 2022
edited by Melody  May 6, 2022
 #2
avatar+122385 
+1

Here's another way

 

Multiply all the constants  on top  and  bottom  =   7 * 2 * 27 * 6              42 *27          21 * 27         

                                                                               __________  =         ______  =    _______  =    

                                                                                4 * 2 * 1 * 8                 4 * 8              2 * 8 

 

567 / 16          

 

Now look at  the  rest

 

The first  fraction   gives us   x^(2014 -2013)  =  x^1

The second fraction gives us x^(2012 - 2007) = x^5

The third fraction gives us    x^(2006 - 2002)  = x^4

And the last one  gives us     x^(2008 -2010) =x^(-2)

 

So

 

x * x^5 * x^4 * x^(-2)  =  x^( 1 + 5 + 4 - 2)  =  x^8

 

So...our  answer is  just     (567 / 16) x^8

 

 

 

cool cool cool

 May 6, 2022
edited by CPhill  May 6, 2022

10 Online Users

avatar